Vol. 194 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2018): International Youth Scientific Conference, April 24-26, 2018, Tomsk, Russia; [proceedings]; MATEC Web of Conferences - Kuznetsov G. V. Geny Vladimirovich; Bulba E. E. Elena Evgenievna; Feoktistov D. V. Dmitriy Vladimirovich (Les Ulis, EDP Sciences, 2018)
Title screen